2012
DOI: 10.1074/jbc.m111.323311
|View full text |Cite
|
Sign up to set email alerts
|

MUC1-C Oncoprotein Induces TCF7L2 Transcription Factor Activation and Promotes Cyclin D1 Expression in Human Breast Cancer Cells

Abstract: Background: MUC1-C oncoprotein has been linked to ␤-catenin-dependent gene activation by mechanisms that are unclear. Results: MUC1-C binds directly to the TCF7L2 transcription factor and recruits ␤-catenin to the cyclin D1 promoter. Conclusion: MUC1-C induces cyclin D1 expression in breast cancer cells by activating TCF7L2-mediated transcription. Significance: Targeting MUC1-C function down-regulates cyclin D1 overexpression in breast cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 41 publications
2
83
1
Order By: Relevance
“…22,23 In concert with MUC1-C-mediated stabilization of b-catenin, silencing MUC1-C in MM cells is associated with decreases in b-catenin and slowing of growth. 24 These and other findings in breast cancer cells 25 have linked MUC1-C to activation of WNT/b-catenin signaling and the induction of WNT target genes. Significantly, the MUC1-C cytoplasmic domain also contains a CQC motif that is necessary for MUC1-C homodimerization and for localization of MUC1-C to the nucleus.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…22,23 In concert with MUC1-C-mediated stabilization of b-catenin, silencing MUC1-C in MM cells is associated with decreases in b-catenin and slowing of growth. 24 These and other findings in breast cancer cells 25 have linked MUC1-C to activation of WNT/b-catenin signaling and the induction of WNT target genes. Significantly, the MUC1-C cytoplasmic domain also contains a CQC motif that is necessary for MUC1-C homodimerization and for localization of MUC1-C to the nucleus.…”
Section: Introductionmentioning
confidence: 83%
“…Previous work demonstrated that MUC1-C binds directly to TCF4 and forms a complex with TCF4 on the cyclin D1 promoter in breast cancer cells. 25 Moreover, MUC1-C promoted TCF4-mediated CCDN1 transcription by the recruitment of b-catenin. 25 In the present studies of MM cells, we found that MUC1-C occupies the MYC promoter in a complex with b-catenin/TCF4 (Figure 7).…”
Section: Muc1-c Correlates With Myc Expression In Primary MM Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, its interactions with MUC1 have been shown to promote transformation, primarily through MUC1-β-catenin protein complexes driving transcription of such genes as cyclin D1. 97 In addition, a study by Yuan et al demonstrated that the downregulation of MUC1 promoted E-cadherin/β-catenin complex formation, reduced nuclear β-catenin, upregulated both E-cadherin and β-catenin expression, and decreased invasive potential in PANC1 pancreatic cancer cells and MCF-7 breast cancer cells.…”
Section: Molecular Mechanisms Of Metastasismentioning
confidence: 99%
“…24,25 MUC1-C also localizes to the mitochondrial outer membrane, where it blocks loss of the mitochondrial transmembrane potential and activation of the intrinsic apoptotic pathway. 10 The mechanistic basis for such an anti-apoptotic effect resides, at least in part, in direct binding of MUC1-C to the BH3 domain of the pro-apoptotic BAX protein.…”
Section: Muc1-c Inhibition Is Effective In Enhancing the Cell Death Rmentioning
confidence: 99%